2011
DOI: 10.1063/1.3656016
|View full text |Cite
|
Sign up to set email alerts
|

Size-affected shear-band speed in bulk metallic glasses

Abstract: Defect-induced solid state amorphization of molecular crystals J. Appl. Phys. 111, 073505 (2012) Notable internal thermal effect on the yielding of metallic glasses Appl. Phys. Lett. 100, 141904 (2012) Sheared polymer glass and the question of mechanical rejuvenation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
3
3
0
Order By: Relevance
“…When the indentation deepens, the area-volume ratio reduces and thus the hardness approaches its bulk value. As for the observed size effect on the shear offset, a similar phenomenon was also observed in uniaxial testing of MGs 44 45 . In view of the similarity, we can rationalize the size effect on the shear offset from two aspects: (1) due to shear localization , there is a dimensional misfit between the planar energy dissipation and volumetric energy release, which can therefore result in the size effect on the shear offset 44 ; (2) if the propagation of the localized shear bands in indentation can be viewed as a stick-slip process, longer shear bands, which commonly correspond to higher sample stiffness, also causes larger shear offsets because of the intrinsic size effect in stick-slip as already discussed in ref.…”
Section: Discussionsupporting
confidence: 75%
“…When the indentation deepens, the area-volume ratio reduces and thus the hardness approaches its bulk value. As for the observed size effect on the shear offset, a similar phenomenon was also observed in uniaxial testing of MGs 44 45 . In view of the similarity, we can rationalize the size effect on the shear offset from two aspects: (1) due to shear localization , there is a dimensional misfit between the planar energy dissipation and volumetric energy release, which can therefore result in the size effect on the shear offset 44 ; (2) if the propagation of the localized shear bands in indentation can be viewed as a stick-slip process, longer shear bands, which commonly correspond to higher sample stiffness, also causes larger shear offsets because of the intrinsic size effect in stick-slip as already discussed in ref.…”
Section: Discussionsupporting
confidence: 75%
“…These strain rate and viscosity values are noted again to be similar to those measured from mm-sized samples [25]. These values of average viscosity of shear band are noted to be different than that of Zhao et al [32] and Liu et al [31]. However, the absolute magnitude of viscosity is not of our interest.…”
Section: Discussionsupporting
confidence: 53%
“…This result is consistent with our work and work of Lewandowski and Greer10 because with rising velocity of shear band friction forces are rising too, and at some point of a large shear offset or near shear band concentration places, the temperature can achieve the melting point of Sn, In or Rose alloy. The results of the work27 are also in good correlation with the work26. The authors found that the temperature rise in a shear band increases with increasing strain rates, demonstrating their strain-rate dependence.…”
Section: Discussionsupporting
confidence: 55%
“…In a recent work by Z. Y. Liu et al27 it was found out that propagation speed of a shear band correlates with the shear offset. This result is consistent with our work and work of Lewandowski and Greer10 because with rising velocity of shear band friction forces are rising too, and at some point of a large shear offset or near shear band concentration places, the temperature can achieve the melting point of Sn, In or Rose alloy.…”
Section: Discussionmentioning
confidence: 96%